Research Of The Multipliing Properties Of Vver Cells - Аsroriddin S. Kоsimov; Jonibek M. Nazirov; Bekhruz X. Мukhammadiyev (Revista Electronica de Veterinaria, 2024)
The purpose of this work is to analyze the properties of VVER cells at elevated nuclear fuel contents using the GETERA-93 program.The objectives of this work are the following:Calculation of fuel burnup with 2, 3 and 4 overloads with a central hole at fuel enrichments of 4.4% and 5%.Calculation of fuel burnup with 2, 3 and 4 overloads with increased fuel content at fuel enrichments of 4.4% and 5%.Analysis of changes in the concentrations of the isotopes 235U, 239Pu, 240Pu, 241Pu during fuel burnout with a central hole and without a central hole at fuel enrichments of 4.4% and 5%.